Codon Optimization and Chaperone Assisted Solubilization of Recombinant Human Prethrombin-2 Expressed in Escherichia coli - SARONOM SILABAN; IMAN PERMANA MAKSUM; SHABARNI GHAFFAR; KHOMAINI HASAN; SUTARYA ENUS; TOTO SUBROTO; SOETIJOSO SOEMITRO (Microbiology Indonesia, 2014)
Prethrombin-2 (PT2) is a thrombin precursor, which plays a role in the conversion of fibrinogen into fibrin during blood clotting process. Previous study reported that the expression of human prothrombin-2 (rhPT2) in Escherichia coli formed inclusion bodies. The aim of this study was to establish a strategy to express a soluble rhPT2 in E. coli. This study was animed to design and codon optimize human prethrombin-2 gene as well as to optimize the expression condition using four strains of E. coli. The codon adaptation index (CAI) of the unoptimized hpt2 gene was 0.336, with 56.8% GC content. After optimization, the CAI of optimized hpt2 became 1.000 with 53.1% GC content. The optimized gene was successfully cloned into pTWIN1 expression vector. Expression analysis indicated that only E. coli ArcticExpress strain could successfully express a soluble recombinant rhPT2 protein, with only part of rhPT2 being expressed in insoluble form. However, the rest of the E. coli strains used in the experiments failed to express the rhPT2 in soluble form. We are deducing that the success in achieving soluble expression was not only due to the availability of chaperonins Cpn60/Cpn10, which played a crucial role in the protein folding in E. coli ArcticExpress strain, but also due to the codon optimization of hpt2 gene.